An analysis of the partial feasibility of a novel cardiac exercise rehabilitation programme for patients suffering from cardiovascular disease - Ross, Tayla Jane (Department of Human Biology, 2023)
Introduction: Substantial research has shown that the inclusion of exercise in cardiac rehabilitation has a favourable effect on many outcome variables, and that exercise should be considered a vital and central component for cardiovascular disease (CVD) rehabilitation. South Africans are facing a growing epidemic of CVD, which has major implications for healthcare services and has placed increasing strain on the already grabbling South African healthcare system. Cost-effective primary and secondary prevention and management strategies are needed to slow down the growing CVD epidemic and relieve strain on health-care systems. The need exists for more evidence to demonstrate that cardiac exercise rehabilitation programmes (CRPs) can significantly reduce readmissions, mortality, comorbidities, and improve quality of life. Aims: The aims of this study were to determine the partial feasibility of a novel CRP in a South African public hospital setting by evaluating the following: 1) The recruitment potential and sample population characteristics of those considered eligible to partake in the exercise component of a novel CRP; and 2) The testretest reliability of the tools utilized for the safe monitoring of the exercise intensity during the prospective CRP. Methods: The recruitment potential and sample population characteristics of the target population were determined via retrospective analysis of a hospital admission patient database spreading over three months. The database was searched for demographic data including age, sex, height, weight, waist circumference and BMI, the admission diagnosis, patient co-morbidities and medications. The test-retest reliability of the monitoring tools was conducted on apparently healthy participants who underwent a series of monitoring measures before and after a 6-min motion test on two separate occasions. The test-retest reliability of each monitoring tool was determined using intraclass correlation coefficients (ICCs), effect size calculation and Bland-Altman plots. Results: One hundred and nine patients (52.2%) were considered ineligible for a CRP, whereas 100 individuals (47.8%) were considered eligible. Significant differences were identified between the eligible and ineligible populations were for four comorbidities and two medications. Twenty-two outcome measures were assessed for reliability, five of which were classified as having “poor” reliability, nine as “moderate”, three as “good” and five as “excellent' according to ICCs. Eighteen measures revealed excellent test-retest reliability, and the remaining 8 measures (Baseline Systolic Blood Pressure; Baseline Diastolic Blood Pressure; Baseline Oxygen Saturation; Immediately Post-Exercise Oxygen Saturation; Immediately Post-Exercise RPE; 5-Minutes Post-Exercise Systolic Blood Pressure; 5-Minutes Post-Exercise Oxygen Saturation; and 5-Minutes Post-Exercise RPE) had showed small effect sizes between 0.2-0.5, which was considered acceptable. Conclusion: The results from the analysis of the recruitment potential from a public hospital setting reveal that approximately 33 patients (100 patients/3 months) will be eligible per CRP intake, and the recruitment potential of eligible patients currently exceeds the prospective resource and staff capacity of the CRP. Further investigation is required to address and resolve the shortcoming in resources to offer the CRP to all eligible participants. The results from the test-retest reliability of the monitoring tools used within the CRP revealed that most of the equipment and measures achieved sound reliability, except for the blood pressure monitors, pulse oximeters and RPE scale. Alternative devices for monitoring blood pressure, oxygen saturation and RPE are recommended.